Treatment of hypertriglyceridemia-induced acute pancreatitis with insulin - Coskun, Ali; Erkan, Nazif; Yakan, Savas; Yildirim, Mehmet; Carti, Erdem; Ucar, Deniz; Oymaci, Erkan (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Hypertriglyceridaemia (HT)-induced pancreatitis rarely occurs unless triglyceride levels exceed 1000 mg/dl. Hypertriglyceridaemia over 1,000 mg/dl can provoke acute pancreatitis (AP) and its persistence can worsen the clinical outcome. In contrast, a rapid decrease in triglyceride level is beneficial. Insulin-stimulated lipoprotein lipase is known to decrease serum triglyceride levels. However, their efficacy in HT-induced AP is not well documented. Aim: To present 12 cases of AP successfully treated by insulin administration. Material and methods: Three hundred and forty-three cases of AP were diagnosed at our clinic between 2005 and 2012. Twelve (3.5%) of these cases were HT-induced AP. Twelve patients who suffered HT-induced AP are reported. Initial blood triglyceride levels were above 1000 mg/dl. Besides the usual treatment of AP, insulin was administered intravenously in continuous infusion. The patients’ medical records were retrospectively evaluated in this study. Results : Serum triglyceride levels decreased to < 500 mg/dl within 2–3 days. No complications of treatment were seen and good clinical outcome was observed. Conclusions : Our results are compatible with the literature. Insulin may be used safely and effectively in HT-induced AP therapy. Administration of insulin is efficient when used to reduce triglyceride levels in patients with HT-induced